Morocco’s Renewable Energy Policy: a Critical Analysis of its Sustainable Competitive Advantage, a Consideration of its Sustainable Development and Provision of Policy Recommendations to Policy Makers - Oumazzane, Tarik (2012)
This management project critically assesses Morocco’s Renewable Energy and Efficiency Policy (hereafter referred to as ‘Policy’) and its contribution to Morocco’s acquisition of a sustainable competitive advantage. The concept of sustainable competitive advantage is to be considered and examined in relation to Porter National Diamond Framework. Equally important, the management project will proceed to critically analyse the ways in which the ‘Policy’ contributes to the kingdom’s sustainable development. The economic, social and environmental concepts, which form sustainable development, will be examined in relation to the Stead & Stead Triple Bottom Line model. Based on this analysis, the management project will conclude by providing policy recommendations to policy decision makers, in addition to identifying opportunities that could be beneficial through further embedding of competitive and sustainable development theories in Morocco’s policy making process. The major aim of this management project is to look at how Morocco could emerge as a regional leader and achieve sustainability in the renewable energy sector. Both the theory of competitiveness and sustainable development are required to be considered in the policy making process.